The Effect of Problem-Based Learning Worksheets on Fifth-Grade Students’ IPAS Learning Outcomes - Shinta Mutiara Dewi; Muhamad Khozinul Huda; Susilawati Susilawati (Journal of Educational Sciences, 2026)
Low student participation and limited use of worksheets remain challenges in fifth-grade Natural and Social Sciences (IPAS) instruction, particularly in lessons requiring problem-solving. This study examined the effect of Problem-Based Learning (PBL)-based student worksheets (LKPD) on students’ cognitive learning outcomes in the water cycle unit. This quantitative study used a quasi-experimental non-equivalent control group design, with students remaining in their existing classes rather than being randomly assigned. The study involved 47 fifth-grade students at SDN 1 Trusmi Wetan, with 23 students in the experimental group and 24 in the control group. Learning outcomes were measured using a validated 20-item multiple-choice test, while an observation sheet assessed learning implementation. After confirming normality and homogeneity, the data were analyzed using descriptive statistics, N-Gain, an independent-samples t-test, and Cohen’s d. The experimental group obtained an average posttest score of 78.91 and an N-Gain of 56.32%, compared with 71.46 and 31.55% in the control group. The groups differed significantly (p = 0.018), and the effect size was moderate, with Cohen’s d = 0.72. These findings show that PBL-based worksheets positively and significantly affect students’ cognitive learning outcomes.